On the Formation of S stars from a Recent Massive Black Hole Merger in the Galactic Center - Tatsuya Akiba; Smadar Naoz; Ann-Marie Madigan (The Astrophysical Journal Letters)
The Galactic center hosts a rotating disk of young stars between 0.05 and 0.5 pc of Sgr A*. The “S stars” at a distance <0.04 pc, however, are on eccentric orbits with nearly isotropically distributed inclinations. The dynamical origin of the S-star cluster has remained a theoretical challenge. Using a series of N -body simulations, we show that a recent massive black hole merger with Sgr A* can self-consistently produce many of the orbital properties of the Galactic nuclear star cluster within 0.5 pc. A black hole merger results in a gravitational-wave recoil kick, which causes the surrounding cluster to form an apse-aligned eccentric disk. We show that stars near the inner edge of an eccentric disk migrate inward and are driven to high eccentricities and inclinations due to secular torques similar to the eccentric Kozai–Lidov mechanism. In our fiducial model, starting with a thin eccentric disk with e = 0.3, the initially unoccupied region within 0.04 pc is populated with high-eccentricity, high-inclination S stars within a few Myr. This formation channel requires a black hole of mass ${2}_{-1.2}^{+3}× 1{0}^{5}\,M_{\odot }$ to have merged with Sgr A* within the last 10 Myr.